JAG1 Mutation in a patient with deletion 22q11.2 syndrome and tetralogy of Fallot. Issue 12 (16th August 2013) - Digilio, Maria Cristina; Luca, Alessandro De; Lepri, Francesca; Guida, Valentina; Ferese, Rosangela; Dentici, Maria Lisa; Angioni, Adriano; Marino, Bruno; Dallapiccola, Bruno
Abstract: Deletion 22q11.2 (del22q11.2) syndrome, also known as DiGeorge/Velo‐cardio‐facial syndrome (DG/VCFS), and Alagille syndrome are genetic disorders characteristically associated with congenital heart defects (CHDs). We report on a patient with tetralogy of Fallot (TOF) and clinical features of DG/VCFS, hemizygous for del22q11.2 and heterozygous for the 2810G > A (p.Arg937Gln) mutation in the JAG1 gene associated with Alagille syndrome. The clinical features of del22q11.2 syndrome are present in the patient, including facial anomalies, typical TOF, speech delay with hypernasal voice, and learning difficulties. TOF and mild hepatic involvement, consisting of slightly elevated aminotransferase conjugated bilirubin levels, were the only features of Alagille syndrome in our patient. The anatomic type of TOF displayed no distinctive recognizable pattern for either DG/VCFS or Alagille syndrome. It is likely that hemizygosity of the TBX1 gene was causally related to TOF in this patient, although a synergistic pathogenic role of the JAG1 gene mutation in causing the heart defect cannot be excluded. JAG1 mutations have been previously detected in patients with nonsyndromic TOF and recent molecular evidence supports the cumulative effect of multiple genetic defects in the etiology of human malformations. We hypothesize that a similar mechanism could be present in this patient with del22q11.2 syndrome associated with a JAG1 missense mutation acting as possible modifier factor for TOF. © 2013 Wiley Periodicals, Inc.